Exploration of Learning Media for Visual Communication Design Expertise Programs in Vocational High Schools: Operational Challenges and the Need for Industry-Based Interactive Media - Wanda Ani Nizar Auliya; Bahrul Dwi Kurniawan; Maraftul Afdilia; Havi Ayuning Tyas; Genta Aldi Saputra (Journal on Smart Learning Technologies, 2026)
The transformation of vocational education in the digital era necessitates the integration of instructional media capable of bridging industry demands with learning processes in schools. This study aims to describe the current use of instructional media in the Visual Communication Design (VCD) program at SMKN 2 Jiwan, identify the challenges encountered in its implementation, and analyze the need for the development of industry-based interactive learning media. The study employed a descriptive qualitative approach with a case study design. Data were collected through observations, interviews, and documentation, and subsequently analyzed using the interactive analysis model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the instructional media currently utilized are still predominantly conventional, including direct demonstrations and static media, which have not fully supported self-paced learning and project-based learning approaches. In addition, limitations in educational facilities and infrastructure, particularly the shortage of practical equipment, constitute a major challenge in the learning process. Existing media are also unable to comprehensively represent industry workflows, especially during the pre-production, production, and post-production stages. On the other hand, students expressed a strong need for interactive, visually rich learning media that can be accessed through mobile devices. The study concludes that the development of digital interactive learning media integrating industry workflows represents a relevant solution for enhancing the effectiveness of vocational learning. Such media are expected to foster students’ learning autonomy, address limitations in practical learning facilities, and improve students’ work readiness through the implementation of the Teaching Factory approach.